Interpreting Qur‘ānic Verses on Religious Moderation in Friday Sermons: An Oral Exegesis Study at At-Taqwa Grand Mosque, Bulakamba, Brebes - Didi Junaedi; Achmad Lutfi; Ali Kresna Jati Winata (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2026)
This article examines how Qur‘ānic verses concerning religious moderation are interpreted in six Friday sermons delivered at At-Taqwa Grand Mosque in Bulakamba, Brebes. Existing scholarship on religious moderation has largely focused on public policy, religious communication, and social harmony, while paying less attention to the interpretive process through which sermons function as oral exegesis. This qualitative study combines the Living Qur‘ān approach, oral exegesis, and contextual interpretation. Its primary data comprise six sermon texts addressing tolerance, national commitment, radicalism, civility, tabayyun (verification), and local culture; observation and interviews are used to clarify the contexts in which the sermons were produced and received. The analysis identifies the cited verses, reconstructs the meanings assigned to them in the sermons, compares these readings with classical and contemporary Qur‘ānic commentaries, and evaluates their patterns of contextualization. The findings reveal three principal patterns. First, Qur‘ān 2:143 and 5:8 are interpreted in a moral-contextual manner to construct a balanced, just, and nonviolent Muslim identity. Second, Qur‘ān 2:256, 49:13, and 49:6 are actualized as foundations for tolerance, recognition of diversity, and the ethics of information verification. Third, the simplification of radicalism, liberalism, Arab culture, and the status of non-Muslims demonstrates the pedagogical and selective limits of oral exegesis. The article argues that Friday sermons constitute an effective arena of public exegesis, but their authority must be accompanied by contextual precision, openness to interpretive plurality, and a clear distinction between the Qur‘ānic message and contemporary social agendas.